Counterexamples in Model Checking - A survey - Debbi, Hichem (Informatica, 2018)
Model checking is a formal method used for the verification of finite-state systems. Given a system model and such specification, which is a set of formal properties, the model checker verifies whether or not the model meets the specification. One of the major advantages of model checking over other formal methods its ability to generate a counterexample when the model falsifies the specification. Although the main purpose of the counterexample is to help the designer to find the source of the error in complex systems design, the counterexample has been also used for many other purposes, either in the context of model checking itself or in other domains in which model checking is used. In this paper, we will survey algorithms for counterexample generation, from classical algorithms in graph theory to novel algorithms for producing small and indicative counterexamples. We will also show how counterexamples are useful for debugging, and how we can benefit from delivering counterexamples for other purposes.